2023
DOI: 10.3390/nu15061429
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fats and Cognitive Status in Italian Middle-Old Adults

Abstract: The increase in life expectancy led to a significant rise in the prevalence of age-related neurological diseases, such as cognitive impairment, dementia, and Alzheimer’s disease. Although genetics certainly play a role, nutrition emerged as a key factor in maintaining optimal cognitive function among older adults. Therefore, the study aimed to investigate whether specific categories and subcategories of dietary fats, based on carbon-chain length, are associated with cognitive status in a cohort of 883 Italian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…[5,11] It has been found that erucic acid is an antioxidant and anti-inflammatory ligand that leads to improved cognitive parameters. [5,12] The effects of erucic acid as a peroxisome proliferator-activated receptor delta (PPAR-δ) ligand have been investigated in rotenone-induced PD model in zebrafish. [13] Erucic acid mediated modulation of membrane composition is associated with complex changes in lipid homeostasis that may affect amyloidogenic processing, providing an important target for lipid-based AD therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[5,11] It has been found that erucic acid is an antioxidant and anti-inflammatory ligand that leads to improved cognitive parameters. [5,12] The effects of erucic acid as a peroxisome proliferator-activated receptor delta (PPAR-δ) ligand have been investigated in rotenone-induced PD model in zebrafish. [13] Erucic acid mediated modulation of membrane composition is associated with complex changes in lipid homeostasis that may affect amyloidogenic processing, providing an important target for lipid-based AD therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Although no data are available concerning the AD‐related alterations of EA in CSF, evidence reveals changes of EA in plasma free FAs and phospholipids from AD and MCI patients 28 . Higher plasma levels of EA were associated with a poorer executive function in elderly people with a parental history of AD, 56 and its consumption was inversely associated with cognitive impairment 57 . Interestingly, in human brain EA content is highly conserved across 13 different brain regions during the ageing process, 58 except in hippocampus, which is a region affected during the initial stages of the disease 59 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Higher plasma levels of EA were associated with a poorer executive function in elderly people with a parental history of AD, 56 and its consumption was inversely associated with cognitive impairment. 57 Interestingly, in human brain EA content is highly conserved across 13 different brain regions during the ageing process, 58 except in hippocampus, which is a region affected during the initial stages of the disease. 59 Since EA crosses the blood‐brain barrier (BBB), 60 these results suggest a possible role of EA in the progression of AD that could be expressed in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) aged 60 and older; (2) living in the nursing home for at least 1 month; and (3) able to communicate. The exclusion criteria included serious psychological impairment or end‐stage illness according to the medical record or participating in other studies or severe cognitive impairment (the Short Portable Mental Status Questionnaire, eight or more errors) 22 . The face‐to‐face interview was conducted by well‐trained researchers in the participants' own room.…”
Section: Methodsmentioning
confidence: 99%